Analysing the contagion effect and governance strategy of corporate financialisation based on a SIRS model - Danfeng Zhang (Taylor & Francis Group, 2021)
Recently, the phenomenon of economic ‘moving from reality to virtual’ has attracted widespread attention. Based on the principle of infectious disease dynamics, this study constructs a SIRS model to examine the contagion effect of corporate financialisation. Using Chinese manufacturing companies as samples, we verify the contagion of corporate financialisation before performing a simulation analysis and proposing strategies to address financial contagion risks. The results shows that corporate financialisation is contagious in the sample companies. This feature depends on the initial contagion conditions and threshold. When the degree of corporate financialisation does not meet the initial contagion conditions and is within the contagion threshold, contagion will not occur. Otherwise, financialisation behaviour will cause mutual contagion and produce a contagious effect. Meanwhile, the higher the contagion and the second conversion rates of financialisation, the stronger the contagion effect. The larger the financial reversal and self-recovery rates, the weaker the contagion effect. Finally, we propose Multi-dimensional governance strategies of financial contagion risk. This study explores the formation mechanism of corporate financialisation from a new perspective to provide ideas for the financial governance of enterprises and promote benign interaction between entities and finance.